Desenvolvimento profissional colaborativo de professores que ensinam matemática nos anos iniciais: entre experiências, práticas e sentidos. - Silva, Jaqueline Ferreira da (Universidade Federal de São Carlos, 2025)
This research, linked to the Graduate Program in Education at the Federal University of São Carlos – Sorocaba Campus, aimed to understand the processes of teacher professional development that emerge from the participation of Early Childhood Education and Elementary School teachers in a study group with collaborative characteristics, focused on the teaching and learning of Mathematics. The guiding question was: Which processes related to professional development emerge from teachers’ participation in collaborative meetings focused on Mathematics Education? To address this question, a study group was established, articulating teaching, research, and outreach activities through face-to-face meetings, synchronous online sessions, and asynchronous interactions in a virtual learning environment. The activities emphasized theoretical studies, reflective writing, and the sharing of pedagogical practices. The theoretical framework was grounded in Wenger (1998) and Lave and Wenger (2002), regarding Communities of Practice, as well as contributions from Day (2001), Nóvoa (1992; 2019), Contreras (2002), Marcelo-García (2009), and Gama (2013), who discuss teacher professional development from a collaborative perspective.The group experienced a collective constitution process, marked by qualified listening, pedagogical co-authorship, and identity strengthening, configuring itself as a space for continuous and situated learning. The results show that the proposal fostered the building of bonds, the re-signification of teachers’ relationship with Mathematics, the circulation of professional knowledge, and the consolidation of innovative practices, based on a formative approach that values concrete experiences, the real challenges of teaching, and the collective production of meaning.Thus, the study points to a broadened conception of collaborative teacher professional development, anchored in negotiation, authorship, and the transformative potential of practices lived within community.
Collaborative professional development of teachers who teach mathematics in the early years: between experiences, practices, and meanings.
Keywords: Desenvolvimento Profissional; Grupo Colaborativo; Formação Continuada Colaborativa; Professional Development; Collaborative Group; Collaborative Continuing Education; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO; 4. Educação de Qualidade